Lantana Toxicity in Grazing Cattle - Govindaiah, Kavitha; Biradar, Rajashekar; Gupta, Venkatesha M Dasappa; Munivenkatappa, Byregowda S (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Lantana Sp. is one of the popular toxic plant and major weeds in many of the countries. It can grow vigorously,invading many areas even at adverse climatic conditions in tropical and sub-tropical areas, damaging field crops. Mostlantana poisoning occurs when stock unfamiliar with the plant are introduced to such areas. Animals tend to avoid grazing oflantana unless forced to eat through lack of adequate food, or sometimes, they eat accidentally while grazing. Younganimals are most at risk. Red flowered varieties are thought to be the most toxic but some white and pink flowered varietiescan also be highly toxic. This poisoning is reported in cattle